Audit Committee Audit Committee and Firm Performance During Covid 19 - azizah, amiril - (Universitas Muhammadiyah Magelang, 2023)
This study aims to analyze the relationship between audit committees and company performance during the Covid-19 pandemic. In a crisis situation like this pandemic, it is important to pay attention to the role of the audit committee in improving company performance. The research method used is secondary data analysis from the financial reports of companies listed on the Indonesia Stock Exchange from January 2019 to December 2020. The results of this study show the audit committee characteristic has a positive correlation with Return on Asset (ROA) and Return on Equity (ROE) as proxies for firm performance. Meanwhile, the result audit committee has no significant impact on Tobin.s Q as a measure of firm performance. Data on this research provided 99 companies with a sample population of 396 listed finance and non-finance companies in the Indonesia Stock Exchange. The sample was determined by using purposive sampling. To analyze the panel data used test estimate; pooled Least Square (PLS), Fixed Effect Model (FE), and Random Effect Model (RE) on the STATA program. Results of this study show the audit committee characteristic has a positive correlation with Return on Asset (ROA) and Return on Equity (ROE) as proxies for firm performance. Meanwhile, the result audit committee has no significant impact on Tobin.s Q as a measure of firm performance. Keywords: Number Audit committee, Audit committee independent, the Number audit committee has financial expert, Firm performance